Real world complexities of periodization in a youth soccer academy: An explanatory sequential mixed methods approach. Issue 11 (3rd June 2022) - Pass, Jake; Nelson, Lee; Doncaster, Greg
ABSTRACT: The purpose of the study was to (1) assess the training load experienced during pre-season and in-season meso-cycles within youth academy soccer players and (2) investigate the extent to which the intended periodized approach was implemented, considering those factors that affected its realization. An explanatory sequential mixed-method design comprising two phases was adopted. Phase 1 encompassed the quantitative analysis of training load data, using 10 Hz GPS, and consisted of 17 youth academy soccer players (age 17 ± 1 yrs; stature 179 ± 9 cm; body mass 72 ± 9 kg), from a professional English soccer academy. Phase 2 involved the collection of qualitative data in relation to the data collected in phase 1 of the study. Three semi-structured interviews were conducted with the lead strength and conditioning coach at the same academy, to gain his reflections on the data, its alignments with desired outcomes, and factors that impacted on the enactment of the periodized training programme. The results provide original information on the training load experienced within a youth soccer academy and novel insights into the complex realities of enacting periodized training programmes in practice.